Strengthening student solidarity through the integration of 'sambatan' indigenous knowledge in primary school social studies - Rizky Aulia Rahman; Kirana Prama Dewi (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2026)
This study aims to explain how the sambatan tradition is integrated as a learning resource in elementary school social studies and its contribution to strengthening student solidarity. This study employed a qualitative approach. The research subjects consisted of the school principal, the fourth-grade homeroom teacher, and 23 fourth-grade students. From the total student population, six students were selected for in-depth interviews. Data collection methods included observation, interviews, and documentation. The research findings are presented descriptively by examining the integration of the "sambatan" indigenous knowledge into elementary school social studies to strengthen student solidarity. In the planning phase, the values of sambatan were incorporated into the teaching modules and learning objectives. Meanwhile, in the implementation phase, the integration was carried out through a project-based learning activity called the "local culture love movement" (gerakan cinta budaya lokal), which incorporated sambatan practices where students helped one another, cooperated, and shared responsibilities to complete group assignments. The data analysis technique followed Creswell’s framework, comprising data organization, thorough reading of the data, coding, thematic clustering, and drawing conclusions. The results indicate that integrating the sambatan tradition as indigenous knowledge into social studies successfully nurtured and reinforced solidarity values among fourth-grade students at SD Negeri Korowelang. This was evidenced by the students' increased engagement in group activities, extracurriculars, and school habituation. Thus, the integration of sambatan indigenous knowledge into social studies learning not only enhances students' conceptual understanding but also contributes significantly to improving their sense of solidarity.